(3GdYbdI GdeSJhaRIs - (3eMeO Hf Ydj Hf eMeO Hf YQHj , CHh HcQ GdMGJej GdWGFj GdCfOdSj, GdeYQha HeMjj GdOjf GHf YQHj,J (B638 (3g` s ((3GSeGYjd? s)
(3ChdgG (B:s
(3GdMeO ddg GdhGgH GdPi EaJJM hLhO GdShi EYde Cf Gddg JYGdi Yde faSg aYde GdYGde adPdc NQL Ydi GdUhQI hNdb Gddg YR hLd GdEfSGf eNJUQkG TQjakG LeY ajg JYGdi GdYGde GdcHjQ s
(3BNQgG (B:s
(3aCLGHg GdfGWb HdSGf GdMbGFb Efi YdeJ HCfi ai MaXce EP MaXfG Je GdcJGH HMeO Gddg hYhfg hMSf Jhajbg s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B257s
Keywords: (3CUhd Gdabgs